Blood biomarkers associated to complete pathological response on NSCLC patients treated with neoadjuvant chemoimmunotherapy included in NADIM clinical trial. Issue 7 (19th July 2021) - Laza‐Briviesca, Raquel; Cruz‐Bermúdez, Alberto; Nadal, Ernest; Insa, Amelia; García‐Campelo, María del Rosario; Huidobro, Gerardo; Dómine, Manuel; Majem, Margarita; Rodríguez‐Abreu, Delvys; Martínez‐Martí, Alex; De Castro Carpeño, Javier; Cobo, Manuel; et al.
Abstract: Background: Immunotherapy is being tested in early‐stage non‐small cell lung cancer (NSCLC), and achieving higher rates of complete pathological responses (CPR) as compared to standard of care. Early identification of CPR patients has vital clinical implications. In this study, we focused on basal peripheral immune cells and their treatment‐related changes to find biomarkers associated to CPR. Methods: Blood from 29 stage IIIA NSCLC patients participating in the NADIM trial (NCT03081689) was collected at diagnosis and post neoadjuvant treatment. More than 400 parameters of peripheral blood mononuclear cells (PBMCs) phenotype and plasma soluble factors were analyzed. Results: Neoadjuvant chemoimmunotherapy altered more than 150 immune parameters. At diagnosis, 11 biomarkers associated to CPR were described, with an area under the ROC curve >0.70 and p ‐value <.05. CPR patients had significantly higher levels of CD4 + PD‐1 + cells, NKG2D, and CD56 expression on T CD56 cells, intensity of CD25 expression on CD4 + CD25hi + cells and CD69 expression on intermediate monocytes; but lower levels of CD3 + CD56 – CTLA‐4 + cells, CD14 ++ CD16 + CTLA‐4 + cells, CTLA‐4 expression on T CD56 cells and lower levels of b‐NGF, NT‐3, and VEGF‐D in plasma compared to non‐CPR. Post treatment, CPR patients had significantly higher levels of CD19 expression on B cells, BCMA, 4‐1BB, MCSF, and PARC and lower levels of MPIF‐1 and Flt‐3L in plasma compared to non‐CPR. Conclusions: Patients achieving CPR seem to have a distinctive peripheral blood immune status at diagnosis, even showing different immune response to treatment. These results reinforce the different biology behind CPR and non‐CPR responses. Abstract : 1. Non‐small cell lung cancer (NSCLC) patients achieving complete pathologic response (CPR) after neoadjuvant chemoimmunotherapy seem to have a distinctive peripheral blood immune status at diagnosis and surgery. 2. At diagnosis, CPR patients are characterized by a stronger previously induced immune response with a higher cytotoxic profile and lower levels of inhibitory cytokines and cells. 3. This exploratory analysis of the NADIM study supports the use of blood as a valid source for response biomarkers and may serve as a first step to elucidate response mechanisms to chemoimmunotherapy in NSCLC.